RIFM fragrance ingredient safety assessment, dihydro-α-terpineol, CAS Registry Number 498-81-7. (December 2017) - Api, A.M.; Belsito, D.; Bhatia, S.; Botelho, D.; Browne, D.; Bruze, M.; Burton, A.; Buschmann, J.; Calow, P.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Highlights: Dihydro-α-terpineol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. All endpoints were cleared using target data, read across and/or TTC.